Cosmopolitan orientation of the process of international environmental lawmaking an Islamic law genre - Aḥmad, Ali (University Press of America, 2001)
The process of regulation in the field of international environmental law belies the complexity of environmental issues that need to be addressed in managing global environmental resources. Although the regulatory process has succeeded in elevating the acknowledgement of a new set of ideas and concepts toward sustainable development, it has not had success in elevating those concepts into a set of determinative norms or rules.